The q-Binomial Theorem and two Symmetric q-Identities - Guo, Victor J. W. (The Electronic Journal of Combinatorics, 2003)
We notice two symmetric q-identities, which are special cases of the transformations of _2φ_1 series in Gasper and Rahman’s book (Basic Hypergeometric Series, Cambridge University Press, 1990, p. 241). In this paper, we give combinatorial proofs of these two identities and the q-binomial theorem by using conjugation of 2-modular diagrams.